Subregional analysis of joint stiffness facilitates insight into ligamentous laxity after ACL injury - Wu, Danni; Zhao, Xuan; Wu, Bin; Zhou, Lan; Luo, Ye; Huang, Xiaofan; Xu, Weidong; Wang, Shaobai (Frontiers in Bioengineering and Biotechnology, 2023)
The purpose of this study was to use arthrometer to measure the quantitative indicator of knee laxity, bringing clinicians a new perspective on how to identify injury to the ACL. Anterior tibial displacement under continuous loading was measured using a novel digital arthrometer in 30 patients with unilateral anterior cruciate ligament injury and 30 healthy controls. Load-displacement curves were plotted, using real-time load and displacement changes. Stiffness was defined by the slope of the applied load to tibial displacement. Anterior tibial displacement and instantaneous stiffness values under different loads were compared. Using the minimum stiffness as the turning point, the load-displacement curve was divided into regions 1 and 2. The two regions' stiffness changes were compared. In the anterior cruciate ligament injury group, instantaneous stiffness was significantly lower on the injured side than on the healthy side (P<0.05). Stiffness was significantly lower in the anterior cruciate ligament injury group than in the control group in the two regions (all, P<0.05). Receiver operating characteristic curves were plotted, using changes in stiffness under the two regions in both groups. Stiffness in region 2 had the largest area under the curve (0.94; 95% CI, 0.88-0.99). Using the cut-off value of 9.62 N/mm to detect ACL injury, the sensitivity and specificity were 93% and 82%. Our investigation of ligament stiffness provides novel insights into the properties of knee laxity. Stiffness in the later stages of increased loading <9.62 N/mm could be a valid indicator for identifying knee laxity.